2016
DOI: 10.1055/s-0042-109866
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Subclinical Cardiovascular Disease in Nonfunctional Adrenal Incidentaloma Patients without Traditional Cardiovascular Risk Factors

Abstract: Data regarding cardiovascular risk in patients with non-functional adrenal incidentaloma (NFAI) are limited. The objectives of this study are to investigate markers of subclinical cardiovascular disease like carotid intima media thickness (CIMT), pulse wave velocity (PWV), augmentation index (AIx), soluble CD40 ligand (sCD40L) and leptin levels in NFAI patients without traditional cardiovascular risk factors and healthy control group. This study involved 35 patients with NFAI (11 males, 24 females; mean age, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…According to previous reports, atherosclerosis prevalence is increased in patients with AIs [20]. Markers of subclinical atherosclerosis (such as carotis intima-media thickness or pulse wave velocity) were found in nonfunctioning AIs without traditional cardiovascular risks [21]. In our study, aortic stiffness was increased in patients with AIs, which is shown by decreased strain and distensibility and increased aortic SI.…”
Section: Discussionsupporting
confidence: 69%
“…According to previous reports, atherosclerosis prevalence is increased in patients with AIs [20]. Markers of subclinical atherosclerosis (such as carotis intima-media thickness or pulse wave velocity) were found in nonfunctioning AIs without traditional cardiovascular risks [21]. In our study, aortic stiffness was increased in patients with AIs, which is shown by decreased strain and distensibility and increased aortic SI.…”
Section: Discussionsupporting
confidence: 69%
“…et al demonstrated higher PWV and peripheral and central AIx in patients with NFAI compared to the control group. PWV showed a positive correlation with total cholesterol, triglyceride, and insulin levels [59]. Similar conclusions were drawn by Akkan T. et al who observed higher PWV and AIx adjusted for heart rate in NFAI patients.…”
Section: Arterial Stiffness Indexsupporting
confidence: 88%
“…In Table 2 we summarize all publications included in our review. In the investigated groups of AI patients an increased CIMT was observed, illustrating morphological changes in carotid arteries expressed by intimal hyperplasia and endothelial atherosclerosis, as well as increased PWV or AIx that are the indicators of arterial stiffness [54,55,[58][59][60]63,64]. Endothelial dysfunction in the form of FMD was also observed [55].…”
Section: Final Assessment Of the Available Cvd Markers In Patients Wimentioning
confidence: 77%
“…The majority of patients with T2DM concurrently suffer from cardiovascular disease, primarily atherosclerosis, which is exasperated by high blood glucose levels and dyslipidemia. Cardiovascular disease and T2DM are both top causes of death worldwide [2,3], and further work is necessary to develop new therapies extending patient lifespan.…”
Section: Introductionmentioning
confidence: 99%